Usefulness of Electronic Medical Records Technology for Nurse Managers: A Literature Review - Inggerid Agnes Manoppo; Rr Tutik Sri Hariyati (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Nurse managers play an important role in evaluating medical records through management activities, namely planning, organizing, actuating and controlling (POAC) that are carried out conventionally. Nurse managers play an important role in evaluating medical records through management activities, namely planning, organizing, actuating and controlling (POAC) that are carried out conventionally. Now medical records have evolved into integrative Electronic Medical Records (EMR). This review aims to explore the usefulness of EMS technology for nurse managers. Literature searches use two database sources namely ProQuest and Google Scholar with boolan search "Electronic Medical Records for nurse manager". Identified 9 articles worthy of review. The total participants of the entire article were 1539 people consisting of doctors and nurses (implementers and managers). It found that EMR is very useful for nurse managers, can increase productivity, facilitate the documenting of nursing care and improve the quality of care through an integrated system